Puskesmas Medical Record Information System (Case Study: Gedangan Health Center, Sidoarjo Regency) - Ramadhan, Kasim (Institute of Computer Science (IOCS), 2025)
Puskesmas Gedangan, Sidorajo District, in recording Medical Record and administration of patient visit and data processing to patient still manual, so administrative process takes a little time, either in handling patient, or in case of making report. Medical Record Information System of Gedangan Public Health Center of Sidoarjo Regency, Medical Record Tool, Patient Data, Drug Data, Action Data, Doctor Data, and admin configuration, but the system is not built all the services in Puskesmas Gedangan Sidoarjo District. In this research used the Waterfall method, where the means to analyze the problems that occurred in Gedangan Public Health Center of Sidoarjo Regency and a Medical Record Information system which was immediately implemented in the form of computer based application. The results of research on the application of Medical Record Information System, at Public Health Center of Gedangan Kabuaten Sidoarjo, on the guided performance of the employees, so that the process of health services to the community can be done quickly and avoid the mistakes in making the patient's Medical Record report.